Clinical Significance Of Some Immunological Indices In Children With Cardiomyopathies - Akhmedova D.I., Akhmedova N.R., Rakhmatullaev A.A. (International Journal of Advanced Science and Technology, 2020)
The article presents the results of studies of 104 patients with cardiomyopathies. As a result of studies, it was found that in children with cardiomyopathies there is an increase in the levels of TNF-α, VEGF, interleukins (IL-1, IL-6 and IL-8), which are directly dependent on the stage of cardiac failure and hypoxia and determine the intensity of myocardial remodeling processes. In children with dilated cardiomyopathy, there is a direct dependence of the degree of LV dilatation on the level of IL-1 and IL-8, the final diastolic size on the concentration of IL-1, the final diastolic volume on the level of IL-8 and the inverse relationship between the parameter of the exile fraction and IL-6 .